2019
DOI: 10.33073/pjm-2019-031
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Antibodies Against Leptospira interrogans Serovar hardjo in Serum Samples from Cattle in Ukraine

Abstract: The article presents data on serological studies of 573 sera samples of cattle that were collected from the farms affected by leptospirosis in different regions of Ukraine in the period of 2014–2015. Samples were investigated by the microscopic agglutination test (MAT), which was conducted within eight serological groups of Leptospira and nine serovars: Sejroe (serovars polonica and hardjo), Hebdomadis (serovar kabura), Tarassovi (serovar tarassovi), Pomona (serovar pomona), Grippotyphosa (serovar grippotyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…The cut-off value (i.e. the threshold that defines whether a test result is positive or negative) for the MAT was provided in 31/36 (86.1%) studies and was highly variable, ranging between 1:5 and 1:1,000 [57, [59][60][61][62][63][66][67][68]71,[73][74][75][76][77][78][79][82][83][84][85][86][87][88][89][90][91][92]94,96,98]. Similarly, the number of serovars included in the MAT panel (mentioned in 28 studies) showed large disparities (min.…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cut-off value (i.e. the threshold that defines whether a test result is positive or negative) for the MAT was provided in 31/36 (86.1%) studies and was highly variable, ranging between 1:5 and 1:1,000 [57, [59][60][61][62][63][66][67][68]71,[73][74][75][76][77][78][79][82][83][84][85][86][87][88][89][90][91][92]94,96,98]. Similarly, the number of serovars included in the MAT panel (mentioned in 28 studies) showed large disparities (min.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…= 1; max. = 24 strains), with a median of 10.5 strains per panel [57, [59][60][61][62][65][66][67]71,72,74,75,[77][78][79][81][82][83][84][85][87][88][89][90][91][92]94,95].…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been an increasing change in the aetiological structure of leptospirosis in farm animals in Ukraine, namely: the detection of new serogroups of Leptospira that have not been previously registered. Thus, cases of bovine leptospirosis caused by the serovar hardjo have been recorded in Ukraine only since 2014 (Pyskun et al 2019).…”
mentioning
confidence: 99%